Spectral encoding method for measuring the relative arrival time between x-ray/optical pulses - Bionta, M. R.; Hartmann, N.; Weaver, M.; French, D.; Nicholson, D. J.; Cryan, J. P.; Glownia, J. M.; Baker, K.; Bostedt, C.; Chollet, M.; Ding, Y.; Fritz, D. M.; et al. (Review of scientific instruments, 2014)
The advent of few femtosecond x-ray light sources brings promise of x-ray/optical pump-probe experiments that can measure chemical and structural changes in the 10–100 fs time regime. Widely distributed timing systems used at x-ray Free-Electron Laser facilities are typically limited to above 50 fs fwhm jitter in active x-ray/optical synchronization. The approach of single-shot timing measurements is used to sort results in the event processing stage. This has seen wide use to accommodate the insufficient precision of active stabilization schemes. In this article, we review the current technique for “measure-and-sort” at the Linac Coherent Light Source at the SLAC National Accelerator Laboratory. The relative arrival time between an x-ray pulse and an optical pulse is measured near the experimental interaction region as a spectrally encoded cross-correlation signal. The cross-correlation provides a time-stamp for filter-and-sort algorithms used for real-time sorting. Sub-10 fs rms resolution is common in this technique, placing timing precision at the same scale as the duration of the shortest achievable x-ray pulses.